Artificial Intelligence in Aircraft Docking: The Fear of Reducing Ground Marshalling Jobs to Robots and Way-Out - Adetayo Olaniyi, Adeniran; Olufunto Adedotun, Kanyio (American International Journal of Multidisciplinary Scientific Research, 2018)
This study gaudily examines the impact of Artificial Intelligence on aircraft docking, and technophobia that may arise on the part of ground marshallers. Ground marshallers are ground personnel that signal or communicate visually to pilots when docking the aircraft in an airport. Artificial Intelligence is an expert system which can be incorporated in different areas, such as finance, transportation, aviation, and tele-communications. Attitude theory and Technology Acceptance Model (TAM) were used to establish the acceptance of Artificial Intelligence. It should be noted that expert systems make decisions which requires human level of expertise. In order to reduce the fear that technology will replace the jobs of human in the field of air transportation particularly with aircraft docking, it is crucial for airport personnel to embrace the upcoming revolution by developing themselves as regard Artificial Intelligence; Universities should prepare the transport students to face the upcoming reality. Also various organizations should put in place necessary resources needed to be part of this revolution which will be fully achieved in the fourth indus-trial revolution and the fifth industrial revolution.